Informal Learning: The Design and Development of an Exhibition - Martin, Daniel; Hokanson, Brad (International journal of designs for learning, 2022)
This paper describes the development and execution of an exhibition in an academic museum setting. The exhibitionis presented as a self-directed learning intervention. The development process included conceptual development, the selection of exhibition materials, the creation of didactic written materials, spatial arrangement of the materials, organizing the flow and interaction of the exhibition, and analysis of the results of the exhibition. We find that interactivity is a viable means to drive interest in the subject(s) of an exhibition and that crowds can make informed decisions about the perception of displayed objects. We propose that interactive didactic exhibitions such as this show potential for successful self-directed learning in a variety of contexts and that further study of the results of such exhibitions are necessary.